2000
DOI: 10.1074/jbc.275.7.4937
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of RNA Molecules That Inhibit the Activity of Ricin A-chain

Abstract: The cytotoxin ricin disables translation by depurinating a conserved site in eukaryotic rRNA. In vitro selection has been used to generate RNA ligands (aptamers) specific for the catalytic ricin A-chain (RTA). The anti-RTA aptamers bear no resemblance to the normal RTA substrate, the sarcin-ricin loop (SRL), and were not depurinated by RTA. An initial 80-nucleotide RNA ligand was minimized to a 31-nucleotide aptamer that contained all sequences and structures necessary for interacting with RTA. This minimal RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 43 publications
3
73
1
1
Order By: Relevance
“…Therefore, selection of aptamers which specifically recognize ricin and can be used as biocomponents in biosensors (aptasensors) should be paid more attention. Hesselberth et al [36] have gained aptamers which have high affinity with ricin A chain. But, they are RNA ligands, and have a very short lifetime in biological fluids.…”
Section: Selection Of Ricin Aptamersmentioning
confidence: 99%
“…Therefore, selection of aptamers which specifically recognize ricin and can be used as biocomponents in biosensors (aptasensors) should be paid more attention. Hesselberth et al [36] have gained aptamers which have high affinity with ricin A chain. But, they are RNA ligands, and have a very short lifetime in biological fluids.…”
Section: Selection Of Ricin Aptamersmentioning
confidence: 99%
“…1). In heterogeneous methods, L is separated from L?T on the surface of a solid substrate, such as a filter, chromatographic support, or a sensor [7][8][9]. In homogeneous methods, L is separated from L?T in solution based on differences in the mobility of L and L?T.…”
Section: Heterogeneous Vs Homogeneous Methodsmentioning
confidence: 99%
“…[18] The RNA aptamers were generated via 9 selection cycles using the NC filter partitioning approach. Upon analysis of the obtained selected aptamers, it was observed that the sequences bear no resemblance to its usual target ribomsal RNA substrate.…”
Section: Ricin Toxin (Cat-b Pathogen)mentioning
confidence: 99%